Human Capital and Women Entrepreneurs in Tye and Dye Micro-Business in Ogun State, Nigeria (Global Journal of Human-Social Science, 2026)
Human Capital has been considered as critical and crucial to women entrepreneurial development. It is argued that where womenfolk are generally disadvantaged educationally in developing countries, other variables of human capital are likely to be brought into their businesses. This paper, therefore, attempts to make a sociological survey of the human capital of women entrepreneurs in Tye and Dye business in Nigeria. To this end, three research instruments were utilized : Questionnaire, Key-Informant Interview, and Observation. The rationale for adopting the three methods was to enrich the quality of data collected. The sample size for this study was two hundred women respondents that were chosen through systematic sampling techniques. The data collected was analyzed with simple percentage and frequency distribution. Chi-Square was used to test the hypotheses. The result revealed that most women do not have adequate human capital such as: education and prior training and previous entrepreneurial experiences for the expansion of their micro-business. The hypotheses tested demonstrate that women entrepreneurs do not have adequate access to financial resources and business information for business expansion. The paper recommends that government intervention is necessary for women business expansion in Tye and Dye micro-business.
Keywords: Human Capital; Women Micro-Business; Tye and Dye Business; Nigeria